You Can Get Me: The Urgency of Personal Data Protection in the Era of Financial Technology - Ashshidiqqi SHMH, Ellectrananda Anugerah (International Journal of Law, Human Rights and Constitutional Studies, 2020)
Constitution plan on the Protection of Personal Data has not been a priority though it is a crucial issue, considering the massive existing technology penetration in Indonesia.The existence of a Ministerial Regulation on the Protection of Personal Data also covers only administrative sanctions, not including criminal sanctions for perpetrators of theft and misuse of data. In this research, the comparison of countries that already have a Personal Data Protection Act for their people and the causes for the Indonesian country to take a long time to implement this personal data protection shall be discussed. Besides, the things need to be prepared in the process of educating the community in responding to the Personal Data Protection Act shall also be discussed in this research. How to cite this article: Ashshidiqqi EA. You Can Get Me: The Urgency of Personal Data Protection in the Era of Financial Technology. Int Jour Law Hum Rights Const Stud 2021; 2(1): 20-24.